(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
It is important for students to have the knowledge to make nutritious and safe snack choices. Providing children with an understanding of healthy and unhealthy foods is crucial. We understand that what a person understands can impact their actions and views. Knowledge plays a significant role in shaping behavior. Adequate and high-quality nutritional intake is crucial to support the optimal growth and development of school-age children. Malnutrition can cause disorders in various organ systems in their bodies. At school age, children begin to show a desire to make their own food choices. Holding health education activities regarding healthy snacks and the dangers of unhealthy foods is one solution that can be implemented. Therefore, the author conducted education activities about nutritious foods and healthy snacks for children at a course institution, with the aim of providing knowledge to school-age children studying at the Universal Technology Computer course institution, so that these children understand nutritious foods and healthy snacks and no longer eat or snack carelessly. The methods used were interactive lectures, discussions and questions and answers, pre-test and post-test evaluations. The results of the counseling conducted at the Universal Technology Computer course institution showed that the counseling program was able to improve the knowledge of the participants. The highest score was 86.7% after the counseling, compared to only 20% before the counseling. Therefore, with the knowledge gained, the counseling participants were able to choose nutritious foods and healthy snacks for their consumption.